2017
DOI: 10.1093/ehjci/jex019
|View full text |Cite
|
Sign up to set email alerts
|

Patient-prosthesis mismatch in new generation trans-catheter heart valves: a propensity score analysis

Abstract: There is an increased risk of PPM with 23mm S3-THV in comparison with 23 mm XT-THV. This may be attributable to the additional sub-annular cuff that avoids the risk of PVR. Regarding the increased vulnerability of younger patients to PPM, we provide essential information on the extension of TAVR indication to the younger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“… 12) One small prospective study in France showed that the S3 group had small EOA and EOAI, and that there was more frequent prosthesis-patient mismatch rate in the S3 group compared to that with SXT. 26) Prosthesis-patient mismatch was most frequent in the 23-mm-sized S3 THV in the study.…”
Section: Discussionmentioning
confidence: 68%
“… 12) One small prospective study in France showed that the S3 group had small EOA and EOAI, and that there was more frequent prosthesis-patient mismatch rate in the S3 group compared to that with SXT. 26) Prosthesis-patient mismatch was most frequent in the 23-mm-sized S3 THV in the study.…”
Section: Discussionmentioning
confidence: 68%
“…Compared to the CoreValve, Evolut R yielded a similar EOA (1.90 ± 0.64 vs. 1.88 ± 0.59 cm 2 , P = 0.19) but a slightly higher mean PG (7.9 ± 4.6 vs. 8.6 ± 5.5 mmHg, P < 0.001) in one large registry . Compared to Sapien XT, the next generation Sapien 3 showed a significantly higher transvalvular PG and PPM rate in one study . The authors suggested that the outer annular sealing polyethylene terephthalate skirt, which functions as a blood‐soaked sponge, bulges into the annular space impeding free forward blood flow.…”
Section: Discussionmentioning
confidence: 95%
“…21 Compared to Sapien XT, the next generation Sapien 3 showed a significantly higher transvalvular PG and PPM rate in one study. 22 The authors suggested that the outer annular sealing polyethylene terephthalate skirt, which functions as a blood-soaked sponge, bulges into the annular space impeding free forward blood flow. Our findings, however, suggest that reduced oversizing of Sapien 3 is more to blame for the observed smaller EOA and the higher PPM rate than a specific design feature.…”
Section: The Incidence and Predictors Of Ppm After Tavrmentioning
confidence: 99%
“…Higher incidence of PPM in the newer Sapien 3 valves has been previously reported . Possible causes of higher PPM risk with Sapien S3 valve include less oversizing compared to Sapien XT and the added outer skirt that may contribute to narrowing of the effective orifice area, relative impedance on the systolic blood flow, and therefore, higher risk of PPM, compared with self‐expandable valves. Evolut PRO/R valves employ a supra‐annular implantation approach rather than intra‐annular as in Edwards Sapien valves, which may lead to better postoperative hemodynamics …”
Section: Discussionmentioning
confidence: 77%